Neuroprotection effect of bovine umbilical mesenchymal stem cell-conditioned medium on the rat model of Alzheimer's disease mediated by upregulation of BDNF and NGF and downregulation of TNF-α and IL-1β - Hevi Wihadmadyatami; Muhammad Ali Zulfikar; Herawati Herawati; Srikanth Karnati; Golda Rani Saragih; Dinda Aliffia; Dyah A.O.A. Pratama; Nurrahmi Handayani; Ulayatul Kustiati; Dewi Ratih Tirtosari; Yudy Tjahjono (Open Veterinary Journal)
Background: Neurodegenerative diseases (NDD) are distinguished by impairment and depletion of nerve cells; one of the most common NDDs is Alzheimer's Disease (AD), which can appear in early onset or late onset. In recent years, the secretome or conditioned medium of mesenchymal stem cells provides new hope for improving conditions and preventing AD. One of the secretomes is bovine umbilical mesenchymal stem cells conditioned medium (BUMSC-CM), where BUMSC is predicted to promote neuronal proliferation potentially.